Poverty and prejudice religious inequality and the struggle for sustainable development - Cheeseman, Kathryn; Mader, Philip 1984-; Tadros, Mariz 1975- (Bristol Bristol University Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Freedom of religion and belief is crucial to any sustainable development process, and yet the Sustainable Development Goals (SDGs) pay little attention to religious inequalities. This book offers a comprehensive overview of how efforts to achieve SDGs can be enhanced by paying greater attention to freedom of religion and belief. In particular, it illustrates how poverty is often a direct result of religious prejudice and how religious identity can shape a person's job prospects, their children's education and the quality of public services they receive. Drawing on evidence from Asia, the Middle East and sub-Saharan Africa, the book foregrounds the lived experiences of marginalized communities as well as researchers and action organizations.
Religions- und Glaubensfreiheit ist für jeden nachhaltigen Entwicklungsprozess von entscheidender Bedeutung. Dennoch schenken die Ziele für nachhaltige Entwicklung (SDGs) religiöser Ungleichheit wenig Beachtung. Dieses Buch bietet einen umfassenden Überblick darüber, wie die Bemühungen zur Erreichung der SDGs durch eine stärkere Berücksichtigung der Religions- und Glaubensfreiheit verbessert werden können. Insbesondere veranschaulicht es, wie Armut oft eine direkte Folge religiöser Vorurteile ist und wie die religiöse Identität die Berufsaussichten einer Person, die Bildung ihrer Kinder und die Qualität der öffentlichen Dienstleistungen, die sie erhalten, beeinflussen kann. Basierend auf Erkenntnissen aus Asien, dem Nahen Osten und Afrika südlich der Sahara stellt das Buch die Lebenserfahrungen marginalisierter Gemeinschaften sowie von Forschern und Aktionsorganisationen in den Vordergrund. [Mit KI übersetzt]
Tabellen, Literaturverzeichnisse, Literaturhinweise, Index
In English
Keywords: Pariser Abkommen (2015-12-12); Freedom Of Religion -- Economic aspects; Sustainable Development -- Religious aspects; Glaubensfreiheit; Religionsfreiheit; Armut; Minderheit; SOCIAL SCIENCE / Poverty & Homelessness; Erde